HUBUNGAN DUKUNGAN KELUARGA DENGAN DEPRESI PADA PASIEN PENYAKIT GINJAL KRONIK DI RUANGAN HEMODIALISA BLU RSUP Prof. Dr. R D. KANDOU MANADO - Saraha, Suryaningsih M.; Kanine, Esrom; Wowiling, Ferdinan (JURNAL KEPERAWATAN, 2013)
Absract: Depression is a form of emotional disorder that show depressed feelings, sad, worthless, meaningless, don’t have morale and pessimistic about the future felt by individuals. The purpose of this research is to know the relation of support families with depression in patients with chronic kidney disease. The research was carried out by the method of cross-sectional study, a sample of 59 respondents comprised of families and patients. Data collection is done by filling in a questionnaire made by researchers and is completed by respondents. Furthermore the data processed using the aid program SPSS for analysis by chi-square testÂ with a level of significance of 0.05 (a).The research results showed that good family support (83.1%) with no depression (79,6%) whereas the depression (20.4%) and less support (16.9%) with depression (70,0%) and no depression (30,0%).Â Conclusion there is a meaningful relationship between family support with the depression, with a value of p = 0,004. Advice for health agencies in hospitals in order to further improve the quality of service to patients in order to prevent the risk of the occurrence of depression in patients with chronic kidney disease. Keywords: Family Support, Depression, Patients PGK Abstrak:Depresi merupakan salah satu bentuk gangguan emosi yang menunjukan perasaan tertekan ,sedih ,tidak berharga, tidak berarti, tidak memiliki semangat dan pesimis tentang masa depan yang dirasakan oleh individu. Tujuan penelitian ini adalah untuk mengetahui hubungan dukungan keluarga dengan depresi pada pasien penyakit ginjal kronik.Penelitian ini dilaksanakan dengan metodecross sectionalstudy, sampel 59 responden yang terdiri dari keluarga dan pasien.Pengumpulan data dilakukan dengan pengisian kuesioner yang dibuat oleh peneliti dan diisi oleh responden. Selanjutnya data diolah dengan menggunakan bantuan program SPSS untuk dianalisis dengan uji chi-square dengan tingkat kemaknaan (a)0.05. Hasil penelitian menunjukan bahwa dukungan keluarga baik (83,1%) dengan tidak depresi (79,6%) sdangkan depresi (20,4%) dan dukungan kurang (16,9%) dengan depresi (70,0%) dan tidak depresi (30,0%). Kesimpulanada hubungan yang bermakna antara dukungan keluarga dengan depresi,dengan nilai p=0,004. Saran bagi instansi kesehatan di rumah sakit agar lebih meningkatkan kualitas pelayanan kepada pasien agar dapat mencegah resiko terjadinya depresi pada pasien penyakit ginjal kronik. Kata Kunci : Dukungan Keluarga, Depresi, Pasien PGK